2022
DOI: 10.20408/jti.2021.0044
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of injuries associated with electric personal mobility devices: a nationwide cross-sectional study in South Korea

Abstract: Purpose: The increasing use of electric personal mobility devices (ePMDs) has been accompanied by an increasing incidence of associated accidents. This study aimed to investigate the characteristics of ePMD-related injuries and their associated factors. Methods: This cross-sectional study was conducted using data from the Emergency Department-based Injury In-depth Surveillance database from 2014 to 2018. All patients who were injured while operating an ePMD were eligible. The primary outcome was the rate of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
5
1
2
Order By: Relevance
“…The rate of helmet use was only 20%, despite the fact that in Korea, protective devices and licenses have been mandatory when riding an e-scooter since May 2021, and this study took place after that. The rate of helmet use seemed to have increased slightly compared to the 3% reported in previous domestic studies [2,7], but it was still low. Legal regulations need to be strengthened.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…The rate of helmet use was only 20%, despite the fact that in Korea, protective devices and licenses have been mandatory when riding an e-scooter since May 2021, and this study took place after that. The rate of helmet use seemed to have increased slightly compared to the 3% reported in previous domestic studies [2,7], but it was still low. Legal regulations need to be strengthened.…”
Section: Discussioncontrasting
confidence: 58%
“…In our study, skull fracture, pneumocephalus, and plastic surgery did not occur at all in the helmet-wearing group. Moreover, there are many reports that using helmets reduces the risk of damage [2,[13][14][15], so it cannot be concluded that wearing helmets is meaningless because this study did not show statistical significance.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations